1998
DOI: 10.1002/(sici)1097-4628(19980926)69:13<2625::aid-app13>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Compatibilization of polypropylene/polystyrene blends with poly(styrene-b-butadiene-b-styrene) block copolymer

Abstract: ABSTRACT:The compatibilizing effect of the triblock copolymer poly(styrene-b-butadiene-b-styrene) (SBS) on the morphology and mechanical properties of immiscible polypropylene/polystyrene (PP/PS) blends were studied. Blends with three different weight ratios of PP and PS were prepared and three different concentrations of SBS were used for investigations of its compatibilizing effects. Scanning electron microscopy (SEM) showed that SBS reduced the diameter of the PS-dispersed particles as well as improved the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
51
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 26 publications
2
51
0
Order By: Relevance
“…SBS was investigated as a compatibilizer for PP/PS blends by some other researchers [23][24][25][26][27][28][29][30][31][32]. By selective localization at the interface of PP/PS blends, SBS is an interfacial agent that can lower the interfacial tension of the PP/PS blends; thereby producing finer and more stable morphologies.…”
Section: Influence Of Pp/ps Volume Ratio and Sbs Additionmentioning
confidence: 99%
See 3 more Smart Citations
“…SBS was investigated as a compatibilizer for PP/PS blends by some other researchers [23][24][25][26][27][28][29][30][31][32]. By selective localization at the interface of PP/PS blends, SBS is an interfacial agent that can lower the interfacial tension of the PP/PS blends; thereby producing finer and more stable morphologies.…”
Section: Influence Of Pp/ps Volume Ratio and Sbs Additionmentioning
confidence: 99%
“…SBS addition was found to compatibilize the CB-filled PP/PS blends. This observation is consistent with that of Radonjic et al [25] for unfilled PP/PS blends compatibilized with SBS.…”
Section: Influence Of Pp/ps Volume Ratio and Sbs Additionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,[18][19][20][21] Studies have also shown that sPS is miscible with atactic polystyrene (aPS). [22][23][24][25] Therefore, these copolymers are expected to be compatibilizers for iPP/sPS blends.…”
mentioning
confidence: 99%